Myelofibrosis Associated, with Rickets, is it Hyperparathyroidism the Triggering Agent or Vitamin D and Hypocalcemia or Hypophosphatemia? - Abdelwahab T H Elidrissy (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2016)
Anemia due to iron deficiency is commonly associated with rickets, but rarely myelofibrosis was seen in infants with rickets in the hypocalcaemic phase. The aim of this review is to elucidate the mechanism of development of myelofibrosis in rickets. We reviewed the literature in PubMed with keywords myelofibrosis, hypocalcemia and anemia. The cases diagnosed as myelofibrosis in infants with evidence of rickets were studied. Hypocalcemia as it occurred in all the cases reported, it suggests that an association exists between  yelofibrosis and hypocalcemia possibly as a consequence of a disturbed vitamin D  etabolism. We could not find another evidence to support a direct relation between low  alcium per se and myelofibrosis. Vitamin D with its multiple metabolites and whose levels in  ur sunny communities are getting lower and lower with more associated diseases being  iscovered still needs to be considered. Hyperparathyroidism is another factor to be iscussed together with hypophosphatemia. Vitamin D role in mast cell proliferation has to be seriously studied and basic research is necessary. Myelofibrosis in rickets seems to be caused by hyperparathyroidism whether primary or secondary. In primary hyperparathyroidism the removal the causing adenoma was followed by complete recovery of the myelofibrosis. Myelofibrosis associated with rickets is very rare but serious and need to be looked for in places where vitamin D deficiency is common.